Protesting Rape in India. Issue 1 (June 2016) - Gomes, Chandan
This photo essay is an account from the perspective of an unknown citizen of the protest movement that happened in Delhi after the rape of a young girl on a bus in the city in December 2012. Chandan Gomes documents the movement not as a documentary photographer or a photo journalist, but as a protestor.